2002
DOI: 10.1093/emboj/cdf418
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-specific platelet-derived growth factor-B ablation mimics diabetic retinopathy

Abstract: Loss of pericytes from the capillary wall is a hallmark of diabetic retinopathy, however, the pathogenic signi®cance of this phenomenon is unclear. In previous mouse gene knockout models leading to pericyte de®-ciency, prenatal lethality has so far precluded analysis of postnatal consequences in the retina. We now report that endothelium-restricted ablation of platelet-derived growth factor-B generates viable mice with extensive inter-and intra-individual variation in the density of pericytes throughout the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
303
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(322 citation statements)
references
References 36 publications
14
303
0
5
Order By: Relevance
“…This results in proliferation and migration of pericytes/VSM cells during maturation of vessels (Betsholtz, 2004;Hoch and Soriano, 2003). Studies show depletion of pdgfb specifically in the endothelium, results in significant pericyte deficiency in the vasculature (Bjarnegard et al, 2004;Enge et al, 2002) whilst similar depletion of pdgfb in hematopoetic or neuronal cells had no effect on the vasculature (Buetow et al, 2001;Enge et al, 2003). These interactions highlight the critical role of endothelium-derived PDGF in pericyte recruitment.…”
Section: Pericyte/vsm-endothelial Cell Interactions In the Tumor Micrmentioning
confidence: 99%
“…This results in proliferation and migration of pericytes/VSM cells during maturation of vessels (Betsholtz, 2004;Hoch and Soriano, 2003). Studies show depletion of pdgfb specifically in the endothelium, results in significant pericyte deficiency in the vasculature (Bjarnegard et al, 2004;Enge et al, 2002) whilst similar depletion of pdgfb in hematopoetic or neuronal cells had no effect on the vasculature (Buetow et al, 2001;Enge et al, 2003). These interactions highlight the critical role of endothelium-derived PDGF in pericyte recruitment.…”
Section: Pericyte/vsm-endothelial Cell Interactions In the Tumor Micrmentioning
confidence: 99%
“…This finding is supported by the fact that PDGF isoforms are established survival factors for pericytes in other non-retinal vascular beds [25]. The role of this growth factor in diabetic retinopathy is also exemplified by the recent report that effective removal of PDGF-BB (as occurs in PDGF-BB null mice) causes depletion of retinal pericytes, an effect which is exacerbated when experimental diabetes is induced in this heterozygous transgenic model [13,29]. During diabetes, AGE cross-linking of the BM may serve to reduce effective transmittance of PDGF isoforms to the pericyte, whether they are derived from serum or secreted by endothelium and/or cells of the retinal neuropile.…”
Section: Discussionmentioning
confidence: 73%
“…In combination with the low replicative capacity of retinal pericytes both in health and during diabetes, AGE-mediated depletion of BM-immobilised growth factors has important survival implications for pericytes and the progression of diabetic retinopathy [25,28,29]. The current study adopted an in vitro model by exposing retinal pericytes to a well-characterised and defined AGE-modified substrate and investigating pericyte replicative capacity and apoptotic death.…”
Section: Introductionmentioning
confidence: 99%
“…A study that inhibited PDGF function in endothelial cells showed a decrease in pericyte recruitment emphasizing the importance of PDGF signaling in promoting stable vessel formation (Enge et al, 2002;Bjarnegard et al, 2004). Another pericyte-endothelial cell interaction involves the Tie2 receptor expressed by endothelial cells and its ligand Ang1 expressed by adjacent pericytes.…”
Section: Pericytes and Vascular Smooth Muscle Cellsmentioning
confidence: 99%